The Effect of Perceived Usefulness on Health Information System Application (ASIK) Use Behavior for Immunization Activities in Makassar City - Nurul Hidayah NR; Yusriani, Yusriani; Samsualam, Samsualam (PT.Mantaya Idea Batara, 2026)
Introduction: One of the important areas of research is evaluating the effectiveness of the Health Information System Application (ASIK) for immunization activities in Makassar City. This study applied the Technology Acceptance Model (TAM) to assess the level of acceptance of the ASIK application in immunization services. The objective of this study was to analyze the effect of perceived usefulness on use behavior, or actual usage, of the ASIK application in immunization activities in Makassar City. A quantitative analytical study with a cross-sectional design was conducted. The study population consisted of 61 immunization officers who used the ASIK application during immunization activities in Makassar City throughout the study period. All eligible immunization officers were included as research participants using a purposive sampling technique based on predefined inclusion and exclusion criteria, resulting in a total sample of 61 respondents. Data were analyzed using the chi-square test with SPSS software to examine the association between variables. The results showed that perceived usefulness of the ASIK application was predominantly positive (95.1%), and use behavior or actual usage of the application was also categorized as positive (96.7%). However, the chi-square analysis indicated no significant association between perceived usefulness and use behavior of the ASIK immunization application (p = 0.903). In conclusion, perceived usefulness did not significantly influence the actual usage behavior of the ASIK application in immunization activities in Makassar City.